Determination of gonad development of mangrove clam Polymesoda expansa (Mousson 1849) by histological classification - Idris, Mohd Hanafi; Abdul Rahim, Azimah; Hamli, Hadi; Nesarul, M. Hoque; Mustafa Kamal, Abu Hena (Academic Journals, 2017)
Background and objective: Mangrove clams are considered as food, collected from the nature. These species deserve special attention for its potentiality. This study was aimed to determine the generative activities of the mangrove clam Polymesoda expansa (Mousson, 1849) and relationship with water quality parameters. Materials and Methods: The reproductive biology of mangrove clam Polymesoda expansa (Mousson 1849) was investigated from October, 2010 to November, 2011 in Kelulit, Miri, Malaysia. Different gonad development stages were classified through histological method which was later on correlated with environmental variables through Pearson Correlation analysis. Results: It was observed that P. expansa is a dioecious clam. Five different gonad development stages in bothmales and females were identified. The Gonad Index (GI) indicated that gametogenesis began in November and by January onwards mature clams were found. Spawning season was identified all the year around mainly during September-December. The highest Gonad Index (GI) value was recorded in September, 2011 for females with 2.0 and it was 1.7 for males in March and November 2011. However, there was no significant difference (p>0.05) in Gonad Index (GI) between the males and females when it was confirmed by Kruskal-Wallis non parametric test. The monthly recorded physico-chemical parameters of estuarine water at sampling site were 2.79±3.15 psu, 5.46±1.34, 29.4±1.3EC, 2.73±1.09 mg LG1 and 283.5±150.5 mm for salinity, pH, temperature, Dissolved Oxygen (DO) and rainfall,respectively. Conclusion: The information gathered from this study indicated that P. expansa is dioecious animal and has continuous gametogenic development through a year. Therefore, P. expansa is able to spawn all the year around regardless on water parameters changes in the habitat.